Multi-objective real-time optimization energy management strategy for plug-in hybrid electric vehicle. (April 2019) - Du, Siyu; Yang, Yiyong; Liu, Congzhi; Muhammad, Fahad
Plug-in hybrid electric vehicle provides remarkable results for emission reduction and fuel improvement in the current driving cycles. With the appropriate energy management strategy, the torque can be split by switching of multiple operation modes to improve fuel economy. However, in the process, not only the noticeable jerk or torque fluctuation, which may result in vibration of the drivetrain and unpleasant driving sensation, but also the frequent motor-start-engine process would be triggered, which is accompanied by extra fuel consumption and abrasion of the clutch. Therefore, high attention should be paid to reduce the excess operating times of the motor-start-engine process and take advantage of multiple operation modes to improve fuel economy in plug-in hybrid electric vehicle. To solve this problem, a multi-objective real-time optimization energy management strategy is proposed. First, the motor-start-engine dynamic model of 2-degree-of-freedom is established. Then, the motor-start-engine process is analyzed based on a large number of real-world data, and the cost of the motor-start-engine process is quantified for optimization. What's more, the optimal torque distribution is realized through the powertrain system. Finally, the proposed strategy is verified by the simulation and experiment platform. Results show that the proposed strategy can greatly improve fuel economy, thereby reducing the excess operating times of the motor-start-engine process.